Information support of effective agricultural land use - О. N. Dolmatova; V. N. Shcherba (Омский научный вестник: Серия "Общество. История. Современность")
Efficient and rational use of agricultural land, provision of the population with agricultural products of its own production is becoming one of the priority tasks of modern social development. The solution of the set tasks is directly related to the formation of sustainable and effective land use, a high-quality land management system, the creation of an information database containing relevant and reliable information about the parameters of lands, their legal, environmental status and economic efficiency of use. However, in conditions of a deteriorating condition and a decrease in the efficiency of land use, it is necessary to develop methodological provisions aimed at the formation of rational land use using modern information technologies. All of the above determines the relevance of the study. The article defines the efficiency of information support for agricultural land use; reflects the shortcomings of obtaining and analyzing information on agricultural land at the regional level; recommendations were given on the development of a land information system for the management of agricultural land, the exchange of information on agricultural land use between the subjects of land management, the creation of a unified geoinformation database in the field of agro-industrial complex.